Quantum confinement-tunable intersystem crossing and the triplet state lifetime of cationic porphyrin–CdTe quantum dot nano-assemblies1. Issue 38 (11th May 2015) - Ahmed, Ghada H.; Aly, Shawkat M.; Usman, Anwar; Eita, Mohamed S.; Melnikov, Vasily A.; Mohammed, Omar F.
<x xml:space="preserve">Abstract</x> We show the possibility of modulating the triplet-state lifetime of cationic porphyrins on the surface of CdTe quantum dots.